Understanding the Evolution of Entrepreneurial Learning: A Bibliometric Overview - Fadli Agus Triansyah; Hari Mulyadi; Endang Supardi; Baandaalr Lizein (Program Doktor Ilmu Manajemen, Universitas Pasundan, Indonesia, 2023)
This research aims to conduct a bibliometric analysis of